La naturaleza de la capitalización de créditos en la Sociedad Anónima - Herrada Bazán, Víctor (Revista de Derecho, 2019)
This paper examines capital increase by credit compensation in stock corporations, regulated by article 202 LGS, in terms of one of the most controversial issues that Spanish doctrine has raised: its legal status. This issue brings significant legal consequences in our system. This paper has a brief introduction about the functionality and the structure of the operation, a preliminary issue about what we actually look for when we ask for the legal status of a phenomenon, an analysis of the theories proposed to determine this in credit compensation and, finally, an opinion about it.